‫‫ﻋﻤﻠﻴﺎت ‬‫إدارة‬ ‫اﻟﻤﻌﺮﻓﺔ‬ ‫وﺗﻌﺰﻳﺰ‬ ‫ﺗﻄﻮﻳﺮ‬ ‫اﻟﻤﻨﺘﺠﺎت‬ ‫ﻓﻲ‬ ‫اﻟﻤﺆﺳﺴﺔ‬ ‫دراﺳﺔ‬‫ﻣﻴﺪاﻧﻴﺔ‬ ‫ﺑﺎﻟﻤﺆﺳﺴﺔ‬ ‫اﻟﻮﻃﻨﻴﺔ‬ ﻟﻠﺪﻫﻦ‬ ‫‪-‬‬ - ‬‫ﺧﺪﻳﺠ‫ة دواﻓﻠﻴﺔ‬; ‫ﺻﻔﻴﺔ ‫ﻋﻤﺮي‬‬ (My University, 2019)
The aim of this study is to show the correlation and influence between management processes for Product knowledge and development. The first part dealt with he théorétique aspect in which the study variables were analyzed, knowledge managment processes an independent variable, and product development as a ependent variable. The second part was devoted to the field study conducted at ENAP. The researchers relied mainly on the distribution of a questionnaire on sample of 40 individuals, and retrieved 36 form of analysis with a response rate of 90% after the analysis on which SPSS was based, the stady concluded: - There is a clear perception among the respondents about the processes of knowledge management and product development in the institution under study. - The study showed that there is a positive correlation between knowledge management processes and product development, and the most important relationship between knowledge storage and product development. - The study also showed that there is a relationship between the processes of knowledge management and product development, and the most important relationship between the process of knowledge storage and product development. .................................................... تهدف هذه الدراسة إلى إظهار العلاقة والتأثير بين الإدارة عمليات معرفة المنتج وتطويره. تناول الجزء الأول الجانب النظري الذي تواجدت فيه متغيرات الدراسة تحليلها، وعمليات إدارة المعرفة كمتغير مستقل، والمنتج التنمية كمتغير تابع. أما الجزء الثاني فقد خصص للدراسة الميدانية التي أجريت في ENAP. واعتمد الباحثان بشكل رئيسي على توزيع استبانة على عينة مكونة من 40 شخصا الأفراد، وتم استرجاع 36 نموذج تحليل بنسبة استجابة 90% بعد التحليل والذي استند عليه برنامج SPSS، خلصت الدراسة إلى ما يلي: - يوجد تصور واضح لدى أفراد العينة حول عمليات المعرفة إدارة وتطوير المنتجات في المؤسسة محل الدراسة. - أظهرت الدراسة أن هناك علاقة ارتباطية إيجابية بين إدارة المعرفة العمليات وتطوير المنتجات، والعلاقة الأكثر أهمية بينهما تخزين المعرفة وتطوير المنتجات. - كما أظهرت الدراسة أن هناك علاقة بين عمليات المعرفة الإدارة وتطوير المنتجات، والعلاقة الأكثر أهمية بين عملية تخزين المعرفة وتطوير المنتجات.‬